Elastic moduli and sound velocity in La1-xSrxMnO 3 (x = 0 to 0.3) - Ewe L.S.; Abd-Shukor R. (2023)
The longitudinal and shear sound velocity in colossal magnetoresistive La1-xSrxMnO3 (x = 0.0, 0.05, 0.15 and 0.3) were measured using the pulse-echo-overlap technique in the temperature range of 80 to 300 K. An abrupt increase in the longitudinal velocity was observed immediately below the insulator-metal transition (Tim) in the x = 0.05 and 0.15 samples. This anomaly shifted towards higher temperature with an increase in Sr content. The absolute velocities (measured at 80 K) increased with Sr content. Hystereses in the longitudinal and shear velocity were observed in the x = 0.05 and 0.15 samples. A step-like longitudinal sound velocity anomaly between 150 K and 220 K during warming and cooling was observed in the x = 0.05 sample. A sudden hardening was observed for longitudinal and shear sound velocity coinciding with second broad resistance peak at temperature below Tim in x = 0.15 sample. The characteristic Debye temperature increases as Sr content was increased, indicating a hardening trend. These results indicate the importance of phonons in the transport mechanism of these colossal magnetoresistive materials. 2010 World Scientific Publishing Company.